(untitled) (Clinics, 2016)
OBJECTIVE: To analyze maternal conceptions about excess weight in infancy and the nutritional status of their preschool-aged children. METHODS: A mixed, exploratory study was performed using semi-structured interviews. Two study groups were defined: a group of 16 mothers of children with excess weight and a group of 15 mothers of eutrophic children. The interviews were submitted to content analysis using CHIC software (Classification Hiérarchique Implicative et Cohésitive¯). RESULTS: The mothers of children with excess weight tended to conceive thin children as malnourished, while those of normal weight children emphasized the influence of family and genetics as determinants of a child’s nutritional status. Although there was a certain consensus among the mothers that an unhealthy diet contributes to the risk of a child developing excess weight, the concept of genetics as a determinant of a child’s nutritional status was also present in the dialogue from the mothers of both groups. This result indicates a lack of clarity regarding the influence of eating behavior and family lifestyle on weight gain and the formation of a child’s eating habits. Both groups indicated that the mother has a decisive role in the eating habits of her child; however, the mothers of children with excess weight did not seem to take ownership of this concept when addressing the care of their own children. CONCLUSION: Differences in conceptions, including taking ownership of care, may contribute to the development of excess weight in preschool-aged children.